Conflict, cod and Calanus: can technology increase trust in management of a contested fishery? - Crosman, Katherine M.; Hayes, Adam L.; Davies, Emlyn J.; Majaneva, Sanna (Frontiers in Marine Science, 2025)
Both the mainstream media and fisheries industry publications have documented extensive contention over the relatively novel commercial fishery for the planktonic copepod Calanus finmarchicus (Calanus) in Norway. Opposition to the fishery is concentrated among coastal cod and herring fishers, in part due to concerns about bycatch of fish eggs and larvae. Here we report results from a scenario-based experiment embedded in a survey of those fishers (n=184). We tested whether the introduction of technologically-enabled real-time bycatch management, either through onboard sampling, underwater imaging, or environmental DNA, would increase support for, or trust in management of, the Calanus fishery versus a control. We find that deployment of underwater imaging increases trust in Calanus management; however, no treatment increases support, which remains very low. Open-ended rationales for self-reported levels of trust indicate that potential ecosystem effects of fishing the bottom of the food web, and mismatched values between fishers and managers, may be of more concern to our sample than the possibility of bycatch.